Pretreatment and reconstruction of three-dimensional images applied in a locking reconstruction plate for a structural analysis with FEA - Freitas, João Paulo O. [UNESP]; de Sousa, Edson A. Capello [UNESP]; Foschini, Cesar R [UNESP]; Santos, Rogerio R [UNESP]; Rahal, Sheila C [UNESP] (Springer Nature, 2015)
The concept about fracture stabilization by compression and the use of locking plates have been the interest of many studies. An understanding of the boneplate construct stability is important for clinical use. Differences in plate geometries and materials have influenced in the results obtained. Thus, the present study evaluated the acquisition of images and geometric reconstruction seeking a more detailed study of its structure through the application of numerical methods such as finite elements. A seven-hole locking reconstruction plate manufactured with stainless steel was used as material model. Acquisition of geometric informationwas obtained from the profile projection method for simplified shapes such as curves and external rays. The micro CT (computed tomography) worked as additional information on details of the structure as volume and validation of data obtained from the projection profile.